Bearing Resistance and Failure Mode of Bolted-layered Cemboard Panels - Norhalim, A. F.; Jaini, Z. M. (International Journal of Integrated Engineering, 2020)
The fabrication of precast slab can be made from wide range of material either neat concrete, foamed concrete or even composite. Until recently, a new interest has been discovered. Instead of wet concrete mixing process in plant, the precast slab can be substituted with fibre cement board or commonly referred as cemboard that meets the specific load requirements with minimum thickness. However, cemboard panel is preferable for lightweight floor system due to its physical strength limitation. Its thickness that relatively small around 15 mm to 25 mm contribute to the drawback and subsequently prohibited the application of cemboard panel as heavyweight floor system. Small specimens are prepared to determine the optimum orientation of bolts and type of bond by analysing the bearing resistance and bond-slip behaviour. It was found that the bearing capacity is governed by polyurethane glue. Meanwhile, the bond-slip behaviour is effectively controlled by the steel bolt. If the steel bolt is solely used as bond mechanism, the bearing capacity will rely on its quantity and capacity and increasing the quantity of steel bolt will eventually lead to the higher value of bearing resistance.